2016
DOI: 10.18488/journal.1/2016.6.1/1.1.80.92
|View full text |Cite
|
Sign up to set email alerts
|

Safety Issues at Selected Shrines/Sacred Groves in Eastern Nigeria

Abstract: Contribution/ OriginalityThis study contributes in the existing literature on safety and security issues at sacred places. It used SWOT Matrix in understanding the efficiency of existing safety measures at the studied sacred sites. The study has succeeded in investigating the implications of tourists/visitors" visits to sacred.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…This made some tourists to entertain fear in visiting the groves. [53], note that some of them are sometimes harmful as some visitors to those places in the past had complained of the harmful nature of such heritage sites. There is need for security check within and around the groves environment.…”
Section: Problems and Challenges Facing The Sacred Grovesmentioning
confidence: 99%
See 1 more Smart Citation
“…This made some tourists to entertain fear in visiting the groves. [53], note that some of them are sometimes harmful as some visitors to those places in the past had complained of the harmful nature of such heritage sites. There is need for security check within and around the groves environment.…”
Section: Problems and Challenges Facing The Sacred Grovesmentioning
confidence: 99%
“…These religions pose very serious risks to the survival of sacred groves. Some of them have the challenge of extinction and misinterpretation from the general public, hence hampering their relevance to the human society [53]. According to [11], the community's sacred grove was destroyed by religious extremists who believed their destiny was tied to the trees there.…”
Section: Problems and Challenges Facing The Sacred Grovesmentioning
confidence: 99%
“…''Nwommo'' is a symbolic expression of the Ibibio people's ancestral spirit with motif trajectory link to geography and social practice of veneration of the dead. [23] observed that the venerations are ascribed to unseen supernatural beings. [24] opined that some dead which are seen as ancestors are being worshipped by some members of the society as they belief that the dead stands and intercede on their behalf.…”
Section: Figure 1 Variations Of Nwommomentioning
confidence: 99%
“…Furthermore, safety concerns for the visitors to the museums are not properly handled using appropriate measures, rather some museum managements tend not to take proper cognisance of these concerns. Some studies have maintained that museums in some African states are deteriorating and this condition jeopardises the gains of museums to national growth and productivity (Nwankwo and Agboeze, 2016;Adeniji and Ekanem, 2013;Fayenuwo and Amusa, 2010;Akpomuvie, 2010, etc.). This paper however, through ethnographic studies, coupled with cluster and purposive sampling techniques, investigated selected museums in the Southeast Nigeria (see Figure 1) to understand issues on safety with respect to sampled museums and role of museum to national reformation.…”
Section: Introductionmentioning
confidence: 99%